(untitled) (Journal of Parents and Teachers, 1995)
The article discusses the paths of life, which are often difficult and misleading, leading to dead-end mazes. It is suggested that happiness depends on the perception of the road traveled. In addition, the possibility of seeing opportunities and dreams as a “lane of stars” is mentioned.